CSUCI Wavelength Vol. 4 No. 18 - Ceal Potts:::::: (California State University Channel Islands)
In this issue: Diet, Nutrition Workshop Planned Islands Café Location Change; Summer Hours for Cafe, Java Hut Reporter seeks information about faculty members' research, projects